DETERMINATION OF WATER QUALITY IN PHYSIC AND CHEMICAL USE STORET INDEX AND POLLUTION INDEX IN COASTAL WATERS DUMAI RIAU PROVINCE - Nur Arifin; Sofyan Husein Siregar; Syafrudin Nasution (AQUASAINS, 2019)
The condition of good water quality is essential to support the survival of organisms that live in it. Determination of the status of water quality needs to be done as a reference in monitoring the water quality pollution.The purpose of this study to analyze and determine the status of water quality physically and chemically in the coastal waters Dumai. The method used in this research is survey method was conducted in December 2018 - April 2019 in the Coastal Water Dumai in Riau province. Sampling sites physical and chemical parameters determined by purposive sampling. Based on consideration of environmental conditions and Dumai City Regulation No. 11 In 2002, it was determined sampling consisted of four stations, with each station there are 5 sampling points were used as replicates. Determining the status of water quality using storet index and the index of pollution. Water quality measurement results About Coastal Dumai use Storet index and the pollution index shows that the coastal waters of Dumai categorized as Heavy Polluted waters.